Closed-loop control of anesthesia and hemodynamic system: a Model Predictive Control approach. Issue 15 (2021) - Maxim, Anca; Copot, Dana
Abstract: This paper proposes a Model Predictive Control (MPC) approach of both anesthesia and hemodynamic systems. The designed control strategy has been validated on a novel and unique patient simulator. The aim of this paper is to evaluate the feasibility MIMO closed-loop control of anesthesia and hemodynamic variables taking into account the interaction (synergic and antagonistic) between subsystems. The proposed methodology takes into account patient variability, is robust to subsystems interaction and meets the clinical objectives. The algorithm is tested in simulation on a hypnosis-hemodynamic combined model for use during general anesthesia. The preliminary results are promising and show the effectiveness of the control procedure.